Electrochemical and Biological Performance of Biodegradable Polymer Coatings on Ti6Al7Nb Alloy - Wojciech Kajzer (Materials, 2020)
The inhibition of the corrosion of metal implants is still a challenge. This study aimed to increase the corrosion resistance of Ti6Al7Nb alloy implants through surface modification, including grinding, sandblasting, and anodic oxidation followed by the deposition of a polymer coating. The aim of the work was to determine the influence of biodegradable polymer coatings on the physico-chemical properties of a Ti6Al7Nb alloy used for short-term implants. Biodegradable coatings prepared from poly(glycolide-caprolactone) (P(GCap)), poly(glycolide ε-caprolactone-lactide) (P(GCapL)), and poly(lactide-glycolide) (PLGA) were applied in the studies. The dip-coating method with three cycles of dipping was applied. Corrosion resistance was assessed on the basis of potentiodynamic studies. The studies were carried out on samples after 30, 60, and 90 days of exposure to Ringer’s solution. Surface topography, wettability, and cytotoxicity studies were also carried out. The degradation process of the base material was evaluated on the basis of the mass density of the metal ions released to the solution. The results indicated the influence of the coating type on corrosion resistance. In addition, a beneficial effect of the polymer coating on the reduction of the density of the released metal ions was found, as compared to the samples without polymer coatings. The obtained results provide basic knowledge for the development of polymer coatings enriched with an active substance. The presence of ciprofloxacin in the coating did not reduce the corrosion resistance of the metal substrate. Moreover, the cytotoxicity test using the extract dilution method demonstrated that the implants’ coatings are promising for further in vitro and in vivo studies.